Carotene Hydroxylase Activity Determines the Levels of Both α-Carotene and Total Carotenoids in Orange Carrots. Issue 5 (23rd May 2014) - Arango, Jacobo; Jourdan, Matthieu; Geoffriau, Emmanuel; Beyer, Peter; Welsch, Ralf
Abstract : High α-carotene levels present in orange carrots correlate with an insertion in the cytochrome P450 carotene hydroxylase gene CYP97A3/lut5 . Overexpression of Arabidopsis lut5 in orange carrots reduces α-carotene and total carotenoid levels as well as the levels of phytoene synthase. This suggests feedback regulation by xanthophyll-derived metabolites acting at levels beyond transcription. Abstract: The typically intense carotenoid accumulation in cultivated orange-rooted carrots ( Daucus carota ) is determined by a high protein abundance of the rate-limiting enzyme for carotenoid biosynthesis, phytoene synthase (PSY), as compared with white-rooted cultivars. However, in contrast to other carotenoid accumulating systems, orange carrots are characterized by unusually high levels of α-carotene in addition to β-carotene. We found similarly increased α-carotene levels in leaves of orange carrots compared with white-rooted cultivars. This has also been observed in the Arabidopsis thaliana lut5 mutant carrying a defective carotene hydroxylase CYP97A3 gene. In fact, overexpression of CYP97A3 in orange carrots restored leaf carotenoid patterns almost to those found in white-rooted cultivars and strongly reduced α-carotene levels in the roots. Unexpectedly, this was accompanied by a 30 to 50% reduction in total root carotenoids and correlated with reduced PSY protein levels while PSY expression was unchanged. This suggests a negative feedback emerging from carotenoid metabolites determining PSY protein levels and, thus, total carotenoid flux. Furthermore, we identified a deficient CYP97A3 allele containing a frame-shift insertion in orange carrots. Association mapping analysis using a large carrot population revealed a significant association of this polymorphism with both α-carotene content and the α-/β-carotene ratio and explained a large proportion of the observed variation in carrots.